(untitled) (diségno, 2022)
The relationship between hand drawing and zoomorphic design can be traced through a non-linear genealogy, which shows different enquiries of artists, artisans and designers into the natural world. It has been precisely the idea of nature that has led the eye and the hand to seek solutions and answers to design questions from different eras. The common thread that binds these experiences, however, is always dictated by the organic forms of plants and animals, which elude the geometric knowledge of architectural representation as consolidated by Albertian Humanism. Late Florentine Mannerism captured the unpredictability of natural forms, which were being collected by naturalists at the same time, and turned them into playful grand-ducal manufactures. After that, unfortunately, some isolated attempts, such as those by Lequeu, were unable to go beyond a superficial and sculptural evocation of animality. It was with Art Nouveau that Gallé and Guimard could read natural shapes as the most suited forms for the materials and decoration of an era that desired to escape from an exhausted historicism. Carlo Mollino was far more aware of the resources that the animal body can show in its anatomical structure, and he used hand drawing in a surprisingly wide range of manners. All these experiences can finally provide a conceptual background for the challenges of recycling and upcycling design in the face of artificial nature created by man in the Anthropocene era.